2014
DOI: 10.1021/jp5063868
|View full text |Cite
|
Sign up to set email alerts
|

Spies Within Metal-Organic Frameworks: Investigating Metal Centers Using Solid-State NMR

Abstract: Structural characterization of metal–organic frameworks (MOFs) is crucial, since an understanding of the relationship between the macroscopic properties of these industrially relevant materials and their molecular-level structures allows for the development of new applications and improvements in current performance. In many MOFs, the incorporated metal centers dictate the short- and long-range structure and porosity of the material. Here we demonstrate that solid-state NMR (SSNMR) spectroscopy targeting NMR-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 93 publications
1
52
0
Order By: Relevance
“…Nowadays, the use of high‐field NMR spectrometers facilitates the SSNMR detection of metal centers in MOFs and zeolites . Huang's group has performed a series of studies on metal centers in MOFs using a 21.1 T high‐field SSNMR spectrometer . They applied 25 Mg NMR to study the local binding environment of magnesium centers in MOFs .…”
Section: Interfaces In Nanoporous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the use of high‐field NMR spectrometers facilitates the SSNMR detection of metal centers in MOFs and zeolites . Huang's group has performed a series of studies on metal centers in MOFs using a 21.1 T high‐field SSNMR spectrometer . They applied 25 Mg NMR to study the local binding environment of magnesium centers in MOFs .…”
Section: Interfaces In Nanoporous Materialsmentioning
confidence: 99%
“…The authors also observed distinct spectroscopic features resulting from adsorbed benzene or dimethylformamide. In their work published in 2014, SSNMR experiments were conducted on a series of “uncommon” quadrupolar nuclei including 49 Ti, 67 Zn, 91 Zr, 115 In, and 139 La. The interpretation of the SSNMR data opened new access to the subtle differences in coordination, bond‐length distribution, and ligand geometry about the metal centers in different MOF materials.…”
Section: Interfaces In Nanoporous Materialsmentioning
confidence: 99%
“…For example, Zn (used in this work) has only one NMR-active isotope ( 67 Zn, I ¼ 5/2) with a relatively low γ and low natural abundance of 4.1% (resulting in a receptivity, relative to 1 H, of 1.18 Â 10 À4 ). Spectral acquisition is further hindered by the presence of a relatively large quadrupole moment (which, coupled with the low γ, produces significant quadrupolar broadening), often necessitating the use of high magnetic fields [19][20][21][22]. Even when resolution is increased through the use of techniques such as MAS, complex and overlapping spectral lineshapes are often still observed in NMR spectra of solids, particularly for disordered materials [23].…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state NMR (SSNMR) experiments have been shown to yield detailed shortrange structural information in a wide variety of materials, including MOFs. [14][15][16][17] Prior studies of MIL-53 (lt) using 1 H and 13 C SSNMR experiments, in conjunction with pXRD experiments, have provided valuable insights into the hydrogen-bonding network between guest H 2 O molecules and the framework. 18 Other nuclei, such as 2 H and 45 Sc, have also been used to probe the MIL-53 system.…”
Section: Introductionmentioning
confidence: 99%